The Realm of Tianfang Advocated by the Daoist Philosophy of Naturalism - Wang, Shaojun (Religions, 2023)
More and more people talk about so-called Daoist ecological thought. Actually, Daoism does not have a ready-made ecological thought. However, it indeed can act as a vital theoretical resource for constructing such thought. In this article, I will argue how this is possible, and what realm Daoism can attain in the relation between human and nature. I will mainly employ such methods as original problem research, literature analysis and comparative research in the inquiry. Compared with traditional Western metaphysics, Daoist ontology can provide stronger philosophical support for the value and significance of empirical things. In addition, Dao does not dominate things like a personal god with will, but gives them the chance to grow and develop according to their own nature. Lao-Zhuang called on people to imitate this character of Dao. They believed that the primitive nature itself was worthy of respect, and urged us to set limits for ourselves and never to distort things’ natural propensities to suit us. Consequently, natural things are neither overshadowed by a noumenon, nor are they subject to humans’ conquering and abuse, so they are capable of flourishing freely. This is precisely the realm of tianfang which Daoism seeks.